1999
DOI: 10.1097/00003246-199904000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Relation of body position at the time of discovery with suspected aspiration pneumonia in poisoned comatose patients

Abstract: The prone position appears to be associated with a lower incidence of SAP than the lateral decubitus position in comatose poisoned patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 15 publications
0
34
0
4
Order By: Relevance
“…• Very-low-quality evidence (downgraded for imprecision) from 1 observational study 98 with 26 subjects showing no difference in plasma volume change (%) at 3 hours after hydration with CE solution; 1 observational study of very-low-quality evidence 99 (downgraded for imprecision) with 26 subjects showing a benefit with CE solution with increased plasma volume change (%) at 4 hours (MD,11; 95% CI,).…”
Section: % To 8% Ce Solution (I) Compared With Water (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…• Very-low-quality evidence (downgraded for imprecision) from 1 observational study 98 with 26 subjects showing no difference in plasma volume change (%) at 3 hours after hydration with CE solution; 1 observational study of very-low-quality evidence 99 (downgraded for imprecision) with 26 subjects showing a benefit with CE solution with increased plasma volume change (%) at 4 hours (MD,11; 95% CI,).…”
Section: % To 8% Ce Solution (I) Compared With Water (C)mentioning
confidence: 99%
“…For the critical outcome of the incidence of aspiration, we identified very-low-quality evidence (downgraded for imprecision) from 1 observational study with a total of 142 patients 11 found in the left lateral decubitus or supine position demonstrating no benefit to being in the left lateral position (relative risk [RR], 0.93; 95% confidence interval [CI], 0.55-1.58). The same observational study had a total of 132 patients found in the right lateral decubitus or supine position and demonstrated no benefit to being in the right lateral position (RR, 1.15; 95% CI, 0.67-1.96).…”
Section: Lateral Side-lying Recovery Position Compared With Supine Pmentioning
confidence: 99%
“…Etliche verschiedene Seitenlagenpositionen sind verglichen worden, aber insgesamt konnten keine signifikanten Unterschiede zwischen ihnen identifiziert werden [812][813][814]. Lagern Sie bewusstlose Personen mit erhaltener Spontanatmung in stabiler Seitenlage und lassen Sie sie nicht in Rücken-lage liegen.…”
Section: Lagerung Einer Bewusstlosen Person Mit Erhaltener Atmungunclassified
“…Four LOE 5 studies 46 -49 supported the lateral recumbent recovery position because it was easier for the rescuer and more comfortable for the victim. One LOE 4 50 and 1 LOE 5 51 study compared the supine to a lateral position and concluded that there was no difference in heart rate variability or in risk for aspiration pneumonia.…”
Section: Treatment Recommendationmentioning
confidence: 99%